2011
DOI: 10.1016/j.mce.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and cachexia: Will treatment with GHSR-1a agonists make a difference for patients suffering from chronic wasting syndromes?

Abstract: Cachexia is a syndrome of wasting and anorexia that worsens the prognosis of many chronic diseases including cancer, chronic kidney disease, chronic heart disease and chronic obstructive pulmonary disease. Properties of the orexigenic hormone ghrelin—including appetite-stimulation, weight-gain production and increased cardiac output—make it a logical treatment for cachexia. While endogenous ghrelin levels are increased in the setting of cachexia, treatment with ghrelin and other GHSR-1a agonists in animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 96 publications
(133 reference statements)
0
29
0
3
Order By: Relevance
“…Ghrelin expression by T cells is also reduced in ageing mice and ghrelin infusion in this model has been shown to reduce levels of IL-6, TNF-α and IL-1β (Dixit et al, 2009). Ghrelin infusion to improve lean body mass and appetite and decrease circulating inflammatory cytokines has had positive outcomes in patient populations with inflammation-related cachexia including cachetic cancer, cardiovascular disease, chronic obstructive pulmonary disease and chronic kidney disease (DeBoer, 2011;DeBoer et al, 2008;Nagaya et al, 2004Nagaya et al, , 2005Strasser et al, 2008). Our finding of increased GHS-R1a availability after exercise and a higher circulating proportion and concentration of GHS-R1a+ lymphocytes in active compared with sedentary individuals suggests that exercise prescription should be explored further as a tool to enhance the effectiveness of ghrelin therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghrelin expression by T cells is also reduced in ageing mice and ghrelin infusion in this model has been shown to reduce levels of IL-6, TNF-α and IL-1β (Dixit et al, 2009). Ghrelin infusion to improve lean body mass and appetite and decrease circulating inflammatory cytokines has had positive outcomes in patient populations with inflammation-related cachexia including cachetic cancer, cardiovascular disease, chronic obstructive pulmonary disease and chronic kidney disease (DeBoer, 2011;DeBoer et al, 2008;Nagaya et al, 2004Nagaya et al, , 2005Strasser et al, 2008). Our finding of increased GHS-R1a availability after exercise and a higher circulating proportion and concentration of GHS-R1a+ lymphocytes in active compared with sedentary individuals suggests that exercise prescription should be explored further as a tool to enhance the effectiveness of ghrelin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are believed to mediate loss of appetite or anorexia commonly associated with inflammation, injury or illness (Kelley et al, 2003) and their overexpression can lead to a catabolic state and cachexia (Dixit and Taub, 2005). With this in mind, acylated ghrelin has been proposed as a promising therapeutic agent for the treatment of a host of cachectic and other chronic inflammatory conditions including cancer cachexia, cardiovascular, respiratory and kidney diseases, inflammatory bowel diseases and ageassociated inflammation (Baatar et al, 2011;DeBoer, 2011;Steinman and DeBoer, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La grelina es una hormona polipeptídica que actúa fijándose sobre los receptores hipotalámicos estimulantes de hormona de crecimiento, incrementando su liberación. Además estimula también la liberación de factores orexígenos, que aumentan del apetito 158 . Paradóji-camente, los pacientes con EPOC y desnutrición pueden tener elevados los niveles de grelina 159 , y los resultados publicados hasta la fecha con la administración exógena de esta sustancia son escasamente concluyentes [160][161][162] .…”
Section: Hormona De Crecimiento Y Grelinaunclassified
“…In addition to its role in normal physiology, ghrelin has been associated with a number of disease processes, including obesity (Scerif et al 2011, Yi et al 2011, type 2 diabetes mellitus and hyperinsulinaemia (Ukkola 2011), gastrointestinal disease (Jeffery et al 2011), cardiovascular disease (Isgaard & Granata 2011), reproductive disorders (Repaci et al 2011), mental health (Steiger et al 2011) and cancer (Chopin et al 2011, Deboer 2011. Ghrelin may play a role in prostate cancer progression, and we have previously demonstrated that ghrelin mRNA and protein is expressed in prostate cancer cell lines and tissues and that ghrelin stimulates cell proliferation in prostate cancer cell lines (Jeffery et al 2002.…”
Section: Introductionmentioning
confidence: 99%